The origin of the Samaritans - Kartveit, Magnar, 1946- (Brill, 2009)
This book evaluates the methods often used for finding the origin of the Samaritans, assesses well known and new material, and suggests that the decisive event was the construction of the temple on Mount Gerizim in the first part of the fourth century b.c.e.
Keywords: Josephus, Flavius -- Knowledge -- Samaritans.; Josephus, Flavius; Bibel -- Pentateuch; Bibel -- Altes Testament -- Prophetische Bücher; Qumrantexte; Josephus Flavius; Ioudaikē archaiologia.; Altes Testament.; Qumrantexte.; Josephus, Flavius.; Könige <Buch, II.> 17.; Antiquitates Judaicae.; Samaritans -- Origin.; Samaritain (peuple) -- Flavius Josèphe. "Antiquités judaïques."; samaritain (peuple) -- origines -- 7e s -- document.; Samaritains -- Origines.; RELIGION -- Judaism -- General.; Samaritans; Entstehung; Jüdische Literatur; Samaritaner.